2019
DOI: 10.1021/acs.iecr.9b03800
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Hydrogen Sulfide from Gas Streams Using Porous Materials: A Review

Abstract: Removal of hydrogen sulfide (H2S) released from various source processes is crucial because this compound can cause corrosion and environmental damage even at low concentration levels. The porous materials offer a wide variety of chemical architectures with tunable pore size and high surface area that are very promising for the adsorption of H2S molecules. This review attempts to comprehensively compile the current studies in the literature on hydrogen sulfide removal in gas purification processes using highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(65 citation statements)
references
References 170 publications
(248 reference statements)
0
60
0
Order By: Relevance
“…59 MOFs have been visualised for the capture of H 2 S; however, most of them have shown poor chemical stability in its presence. 60 Nonetheless, chemically stable MOF materials have demonstrated promising results in the reversible capture of H 2 S. 61 This section highlights outstanding MOF materials that have shown high H 2 S capture performances and in situ H 2 S transformations, as well as biomedical applications.…”
Section: Hydrogen Sulphidementioning
confidence: 99%
“…59 MOFs have been visualised for the capture of H 2 S; however, most of them have shown poor chemical stability in its presence. 60 Nonetheless, chemically stable MOF materials have demonstrated promising results in the reversible capture of H 2 S. 61 This section highlights outstanding MOF materials that have shown high H 2 S capture performances and in situ H 2 S transformations, as well as biomedical applications.…”
Section: Hydrogen Sulphidementioning
confidence: 99%
“… 28 Generally, zeolites containing lower Si/Al ratios tend to adsorb polar substances and are more hydrophilic, while zeolites with higher Si/Al ratios are hydrothermally stable and more hydrophobic in comparison and thus can potentially favor the adsorption of nonpolar molecules. 29 , 30 …”
Section: Introductionmentioning
confidence: 99%
“…To predict these basal interactions density functional theory (DFT) and grand canonical Monte Carlo simulations (GCMC) have been widely implemented by numerous works, as will be discussed throughout the text below. Although the topic of desulfurization using MOFs has been thoroughly reviewed in the past [41][42][43][44][45][46][47][48], the work presented herein is the first to collect and critically review all works found in the literature that focus exclusively on H 2 S capture. As such, attention has been paid to the structural characteristics of these materials that provide significant advantages in H 2 S selectivity and separation, but also to issues related to the reversibility of the process.…”
Section: And Alomentioning
confidence: 99%